Musical-Poetic Allegories of the Vocal-Instrumental Cycle “The Bestiary or Procession of Orpheus” by Louis Durey and Guillaume Apollinaire - Aleksandrova, Oksana Aleksandrovna; Krasnoshchok, Kateryna (Journal of History Culture and Art Research, 2020)
The present work examines a work of art that is unique in its synthetic essence – the vocal-instrumental cycle called “The Bestiary or Procession of Orpheus” by L. Durey, which was based on the texts of the poem of the same name created by G. Apollinaire. The relevance of this research lies in the fact that on the basis of the literary and artistic original source created by G. Apollinaire and its composer’s interpretation by L. Durey, new facets of French modernism in the art of the 20th century are revealed. The subscript translation of the poems from “The Bestiary” by G. Apollinaire represents the poetic semantics that was developed in the musical dramaturgy of the composition by L. Durey. The vocal-instrumental cycle is explored at several levels: the historical context, the artistic concept of the authors (the literary original source by G. Apollinaire and its composer’s interpretation by L. Durey), the analysis of intonation dramaturgy, as well as the peculiarities of meaning – and form-building. In the course of the analysis, the crosscutting leit-intonemes and rhythm formulas have been identified. The system of the composer’s remarks – “states” has been considered. The sharp and flat spheres of tonality inclinations have been characterized within the framework of L. Durey’s atonal manner of writing. As a result, the vocal-instrumental cycle “The Bestiary or Procession of Orpheus” appears as a system of musical and poetic allegories that recreate the main idea of the composition: the catharsis associated with comprehending the depth of the power of art, the cognition of the love and beauty of the world, the struggle of worldly vices of an ordinary person and the Human-Poet, the victory of life over death and the achievement of the ideal perception of the world in realizing the great destiny of the Artist-Creator. The allegorical “portraits” of animals reflect not only the essence of a human nature, as it was originally stated in the medieval “Bestiary”, but the spiritual qualities of the Poet-Creator, whose mission, according to the authors, is to lead humanity from darkness to light. The idea of the authors corresponds to the aesthetic canon of Orphism, based on the identification of the author’s “I” with the mythological image of Orpheus. The catharsis, as a path of purification through deep intellectual work, underlies the idea of the cycle: the spiritual level of the Poet must correspond to his high purpose.